Atividade antifúngica in vitro dos óleos essenciais de Coriandrum sativum L. (coentro) e Foeniculum vulgare Mill. (funcho) sobre cepas de Cryptococcus neoformans - Queiroz, Everton Oliveira de (2012)
Cryptococcus neoformans is yeast capable of causing infection in humans called cryptococcosis that primarily affects immunocompromised patients. The infection usually affects the central nervous system causing meningoencephalitis with a severe and fatal evolution, accompanying or not, lung injury, fungemia and secondary outbreaks on the skin, bones and kidneys. The drugs of choice for treatment are usually amphotericin B associated with 5-flucytosine, however, increasing resistance to antifungal agents available and toxicity caused by them lead the search for new antifungals, becoming natural products as focus of studies in the research of substances with antifungal properties. Thus, the study aimed to investigate the antifungal activity of essential oils of Coriandrum sativum L. (coriander) and Foeniculum vulgare Mill. (fennel) in vitro against 14 strains of Cryptococcus neoformans. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) were determinated by the microdilution technique, and the effects of essential oils on the morphology and time-kill curve of C. neoformans were evaluated. Was found for the essential oil of C. sativum MIC= 64 μg/mL and MFC= 64 μg/mL, and for the essential oil of F. vulgare, MIC= 256 μg/mL and MFC= 512 μg/mL. There were no changes in the morphology of LM 310 and ICB 59 strains of the yeast when subjected to contact with essential oils. Has been observed a decrease in count of viable forms with increasing concentrations of essential oils. In the time-kill curve of C. neoformans, compared to the essential oil of C. sativum, was observed fungicidal effect (decrease ≥ 3 log10UFC/mL from the initial inoculation), at 24 hours, at MICx4 for the strain LM 310, and in MICx2 and MICx4, for the strain ICB 59. The essential oil of F. vulgare, for strain LM 310, began fungicidal activity at the time of 4 hours in MICx2 and MICx4, the MIC was fungicidal at 8 hours. The fungicidal activity for the strain ICB 59 began in 4 hours for all concentrations of essential oil (MIC, MICx2 and MICx4). The essential oils of C. sativum and F. vulgare has antifungal activity against strains of C. neoformans, therefore represent a possibility to become new products with antifungal potential in the treatment of cryptococcosis. However, there is need for further studies to search deeper aspects of the essential oils tested, so they can be used in therapy.